2016
DOI: 10.1109/toh.2016.2554120
|View full text |Cite
|
Sign up to set email alerts
|

Non-Colocated Kinesthetic Display Limits Compliance Discrimination in the Absence of Terminal Force Cues

Abstract: An important goal of haptic display is to make available the action/reaction relationships that define interactions between the body and the physical world. While in physical world interactions reaction cues invariably impinge on the same part of the body involved in action (reaction and action are colocated), a haptic interface is quite capable of rendering feedback to a separate body part than that used for producing exploratory actions (non-colocated action and reaction). This most commonly occurs with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
12
1
Order By: Relevance
“…Brown et al found that there was no difference between joint-torque and vibrotactile feedback in a grasp and lift task using a myoelectric prosthesis [16]. Similarly, Brown et al found that there was no difference in kinesthetic feedback delivered to a different part of the body than the part used for exploration (non-colocated) and vibrotactile feedback in a single-DoF spring stiffness discrimination task [29].…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al found that there was no difference between joint-torque and vibrotactile feedback in a grasp and lift task using a myoelectric prosthesis [16]. Similarly, Brown et al found that there was no difference in kinesthetic feedback delivered to a different part of the body than the part used for exploration (non-colocated) and vibrotactile feedback in a single-DoF spring stiffness discrimination task [29].…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al found that there was no difference between joint-torque and vibrotactile feedback in a grasp and lift task using a myoelectric prosthesis [16]. Similarly, Brown et al found that there was no difference in kinesthetic feedback delivered to a different part of the body than the part used for exploration (non-colocated) and vibrotactile feedback in a single-DoF spring stiffness discrimination task [29].…”
Section: Task Performancementioning
confidence: 99%
“…Moreover, haptic feedback has been shown to accelerate the learning of a task in many fields such as surgery [12], rehabilitation [13], and sports [14], [15]. Rendering flight information using haptic feedback on the user's torso could provide a collocated feedback that is more natural and easier to process [16] and help the user to learn at as faster rate.…”
Section: Introductionmentioning
confidence: 99%